Carbapenem-resistant Citrobacter freundii harboring blaKPC−2 and blaNDM−1: a study on their transferability and potential dissemination via generating a transferrable hybrid plasmid mediated by IS6100 - Zhang, Feilong; Li, Ziyao; Liu, Xinmeng; Hu, Yanning; Zhao, Jiankang; Zhang, Yulin; Fan, Yanyan; Lei, Zichen; Yang, Xinrui; Li, Zhihua; Li, Chen; Wu, Yongli; et al. (Frontiers in Microbiology, 2023)
Introduction The increase in clinical Enterobacteriaceae with dual carbapenemase has become a serious healthcare concern. It is essential to characterize the transferability and potential dissemination of blaKPC−2- and blaNDM−1-coharboring carbapenem-resistant Citrobacter freundii (CRCF). Methods Four blaKPC−2- and blaNDM−1-coharboring CRCF strains were collected from our surveillance of the prevalence of carbapenem-resistant Enterobacteriaceae. The isolates were assessed using species identification, antimicrobial susceptibility testing, conjugation assays, whole-genome sequencing, plasmid stability, and fitness costs. Clonality, genome, plasmidome, and phylogeny were analyzed to reveal potential dissemination. Results Three ST523 blaKPC−2- and blaNDM−1-coharboring CRCF strains, collected from the same hospital within 1 month, exhibited high homology (both identity and coverage >99%), implying clonal dissemination and a small-scale outbreak. Moreover, the blaKPC−2 and blaNDM−1 genes were coharbored on an IncR plasmid, probably generated by a blaKPC−2-harboring plasmid acquiring blaNDM−1, in these three strains. Importantly, the IncR plasmid may form a transferable hybrid plasmid, mediated by IS6100 via transposition, with another IncFII plasmid included in the same C. freundii strain. Furthermore, the blaKPC−2 and blaNDM−1 of the fourth CRCF strain are located on two different non-transferable plasmids lacking complete transfer elements. Additionally, throughout the course of the 10-day continuous passage, the genetic surroundings of blaNDM−1 in four CRCF strains were gradually excised from their plasmids after the 8th day, whereas they maintained 100% retention for blaKPC−2. Genome and plasmidome analyses revealed that blaKPC−2- or blaNDM−1-harboring C. freundii were divergent, and these plasmids have high homology to plasmids of other Enterobacteriaceae. Conclusion Clonal dissemination of ST523 blaKPC−2- and blaNDM−1-coharboring CRCF strains was detected, and we first reported blaKPC−2 and blaNDM−1 concomitantly located on one plasmid, which could be transferred with mediation by IS6100 via transposition. Continued surveillance should urgently be implemented.